Association of Serum Melatonin Level with Mild Cognitive Impairment in Type 2 Diabetic Patients: A Cross-Sectional Study. (28th April 2021) - Zhang, Jichen; Lu, Jiancan; Zhu, Hongling; Zhou, Xinglu; Wei, Xijuan; Gu, Mingjun
Abstract : Objectives . Melatonin is an essential neuroendocrine hormone that participates in the regulation of sleep rhythm and cognitive function. This study aimed to determine serum melatonin levels with mild cognitive impairment (MCI) in patients with type 2 diabetes (T2DM). Methods . A total of 247 T2DM patients were recruited in this retrospective study and divided into 75 subjects with MCI and 172 with normal cognition. Cognitive function was evaluated by the Montreal Cognitive Assessment (MoCA). Their blood sample was examined for the level of melatonin and other biochemical parameters. Results . Melatonin concentration was decreased in MCI patients to non-MCI patients (P < 0.001). Melatonin level was negatively correlated with age ( r = −0.202; P = 0.001), diabetes duration ( r = −0.282; P < 0.001), serum HbA1c ( r = −0.195; P = 0.002), hs-CRP ( r = −0.324; P < 0.001), and TSH ( r = −0.184; P = 0.004) levels and positively correlated with MoCA score, serum HDL-C ( r = 0.145; P < 0.001), FT3 ( r = 0.241; P < 0.001), and FT4 ( r = 0.169; P = 0.008) levels. The multivariable analysis indicated that fewer years of formal education, longer diabetes duration, higher serum HbA1c, higher serum hs-CRP, and lower serum melatonin are the predisposing factors for MCI. Conclusion . Lower melatonin level was associated with cognitive impairment in patients with T2DM. Melatonin might serve as a potential protective molecule against cognitive dysfunction in T2DM.